Business Potential Development of Trading Village for Khaw Khunkha Chawna Khunatham Community Enterprise, Yasothon Province - Apibunyopas, Jeerakiat; Lakkanawanit, Pankeawta (Area Based Development Research Journal, 2020)
This study aims to analyze the operational status and business model, which can activate the business potential of Khaw Khunkha Chawna Khunatham Community Enterprise, thus enhancing business with strength, sustainability and competitiveness. The participation between researchers, community leaders and members of the enterprise group was carried out during the research process purposely to share and exchange knowledge. The data of the community enterprise was collected for SWOT analysis and business model creation in order to define strategies and identify important factors in business operations. By joining the project, the community attended training courses and performed study visits that developed capacity in business management for community leaders and members of the enterprise. The community also learns to develop local products and expand their distribution channels both online and offline; hence improving their business skills and competitiveness. The results of the research process are as follows. 1) The products are improved while distribution channels and media used in public relations extended, resulting in more customers and higher incomes. 2) The members have advanced their knowledge and are aware of the importance of online marketing. 3) Accounting system has been enhanced, making it easier for auditing and convenient for production planning and marketing. 4) The local rice mill became standardized, thereby enabling the community enterprise to process high-quality rice, thus increasing business income. In conclusion, our findings indicate that the analysis and improvement of the operational status and business model enhanced the strength, sustainability and competitiveness for the Khaw Khunkha Chawna Khunatham Community Enterprise.